2009
DOI: 10.4049/jimmunol.0901664
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: Inhibitory Effects of CD4 and CD8 on T Cell Activation Induced by High-Affinity Noncognate Ligands

Abstract: It has been proposed that MHC restriction during thymocyte selection is controlled by coreceptor (CD4 or CD8) sequestration of the signaling molecule Lck. We explored this model as a mechanism for preventing peripheral T cell activation due to non-MHC ligand cross-reactivities of TCRs. TCRs that have a range of affinities for a class I MHC ligand were transduced into a T cell hybridoma in the absence or presence of coreceptors. High and intermediate affinity TCRs (KD = 17 and 540 nM) did not require CD8 for T … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…[45][46][47] Lck sequestration from the TCR/CD3 complex plays a role in T cell-positive selection in the thymus, 48 and it has been proposed to regulate ongoing immune responses and to help maintain peripheral tolerance and MHC restriction. [49][50][51] The present findings indicate that coreceptor tuning for MHC-I-restricted T lymphocytes is not only regulated by levels of CD8 on the T cells, but also by the overall levels of MHC-I on the APCs. While low levels of noncognate MHC-I may enhance APC/T-cell interactions by facilitating cell-to-cell adhesion, 52 high levels of noncognate MHC-I decrease T-cell activation.…”
Section: Discussionmentioning
confidence: 55%
“…[45][46][47] Lck sequestration from the TCR/CD3 complex plays a role in T cell-positive selection in the thymus, 48 and it has been proposed to regulate ongoing immune responses and to help maintain peripheral tolerance and MHC restriction. [49][50][51] The present findings indicate that coreceptor tuning for MHC-I-restricted T lymphocytes is not only regulated by levels of CD8 on the T cells, but also by the overall levels of MHC-I on the APCs. While low levels of noncognate MHC-I may enhance APC/T-cell interactions by facilitating cell-to-cell adhesion, 52 high levels of noncognate MHC-I decrease T-cell activation.…”
Section: Discussionmentioning
confidence: 55%
“…A study by Holler & Kranz 4 showed that CD8 generally increased the pMHC complex potency (reduced the EC 50 ). At the extremes, high-affinity pMHC complexes were found to be sufficiently stimulatory without CD8, and pMHC complexes with low affinities (K d > 3 μM) require CD8 in order to stimulate T cells 4,62 . These effects are not a result of cooperative binding, as it has been shown that the binding of TCR and co-receptors to pMHC complexes are independent 63,64 .…”
Section: Altered Peptide Ligandsmentioning
confidence: 99%
“…When the T cells were stained with SIY/K b streptavidin-linked tetramers, no staining was observed with mock T cells, but the majority (60 to >80%) of m33 TCR-transduced and m33 TCR-SCS-transduced T cells were stained. The enhanced affinity of the m33 TCR allows efficient staining with soluble SIY/K b tetramer even in CD4 T cells as it does not require CD8 for binding or activity [25,28]. The surface levels of the TCR-SCS construct were 2- to 5-fold higher than the conventional αβ TCR on the transduced C57BL/6 T cells, consistent with our previous studies using the αβ-negative T cell hybridoma 58 −/− [23].…”
Section: Resultsmentioning
confidence: 99%
“…The m33 full-length TCR, with an affinity of 30nM for SIY/K b [34,28], responds to its target in CD4 or co-receptor negative T cells [25]. Likewise, m33 TCR-SCS was functional in CD4 or CD8 T cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation